Genetic and Epigenetic Modulation of Cell Functions by Physical Exercise - Di Liegro, Italia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
From an evolutionary perspective, our species has relied upon physical activity for most of its history to survive and has had to escape from predators, to scavenge for food, and to use physique to work or build necessary means for everyday life. Physical activity has been part of our evolution and progress since the very beginning and, consequently, our entire body has been programmed to be active physically. In the last 20 years, scientific research has increasingly shown that our ancient survival principle has beneficial effects not only on the cells and organs involved in physical activities but on the metabolism of the entire organism, influencing the homeostasis and integration of all bodily functions, likely stimulating the production of hormones and other regulatory molecules, with each affecting vital signalling pathways. Most of the web of factors involved in molecular signalling upon exercise are suspected to be centrally controlled by the brain, which has been reported to be deeply modified by physical activity. Such complexity requires a multifaceted approach to shed light on the molecular interactions that occur between physical activity and its outcome at a cellular level.